The History of Acculturation: A review article - Elhami, Ali; Roshan, Anita (Universitas PGRI Madiun, 2024)
Migration is a conscious decision that comes with many difficulties and has been a feature of human history since the beginning of time. The process has increased in frequency recently as a result of globalization. These days, a large number of people from less developed or lower-income countries migrate to more developed or higher-income countries to gamble their fate in a new society in the hopes of ameliorating their lot in life, obtaining a more profitable job, raising their kids in a less hazardous environment, or attending top-notch universities. During their experience, they often endure hardships in the target country, such as resettlement stress, racism, unemployment, and/or language difficulties. Hence, the study of acculturation is crucial in understanding how individuals adapt to a new culture and cope with the challenges they may encounter. This article aims to explore the concept of acculturation by looking at existing theories and research on the topic.